2013
DOI: 10.1192/pb.bp.112.039958
|View full text |Cite
|
Sign up to set email alerts
|

Complex needs survey: informing the development of a community recovery and rehabilitation team

Abstract: Aims and methodTo inform the development of a new, recovery-oriented rehabilitation service, identify local needs and create a pathway for appropriate referrals, accelerating the build up of case-load. We surveyed 1353 secondary service users using a purpose-made needs assessment and case identification questionnaire, completed by nominated care coordinators.ResultsSignificant unmet need for rehabilitation and recovery-oriented interventions was found. The results were used to invite referrals, create a case-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Studies have been identified from across WHO regions, but were predominantly conducted in North America and Europe: African Region (Cameroon, The Gambia, Eritrea), the Eastern Mediterranean Region (Egypt), the South-East Asia Region (India, Thailand), the Region of the Americas (Canada, Chile, USA), the Western Pacific Region (Australia, Singapore) and the European Region (Denmark, Germany, UK, Sweden). In terms of study design, a variety of studies have been included, from observational cross-sectional studies [43][44][45][46][47][48][49][50][51] and cohort studies, [52][53][54][55][56][57][58] over secondary data analysis of population studies, 59 descriptions of tool development 60 61 and algorithm development from machine learning, 62 to prospective observational studies [63][64][65][66] and longitudinal studies. [67][68][69][70] Rehabilitation needs screening In total, 24 rehabilitation need screening tools or assessments have been identified from the 31 included papers.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been identified from across WHO regions, but were predominantly conducted in North America and Europe: African Region (Cameroon, The Gambia, Eritrea), the Eastern Mediterranean Region (Egypt), the South-East Asia Region (India, Thailand), the Region of the Americas (Canada, Chile, USA), the Western Pacific Region (Australia, Singapore) and the European Region (Denmark, Germany, UK, Sweden). In terms of study design, a variety of studies have been included, from observational cross-sectional studies [43][44][45][46][47][48][49][50][51] and cohort studies, [52][53][54][55][56][57][58] over secondary data analysis of population studies, 59 descriptions of tool development 60 61 and algorithm development from machine learning, 62 to prospective observational studies [63][64][65][66] and longitudinal studies. [67][68][69][70] Rehabilitation needs screening In total, 24 rehabilitation need screening tools or assessments have been identified from the 31 included papers.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…43 62 73 Some scales 72 and questionnaires 45 52 53 59 71 are, however, self-administered, or respondents may be care coordinators such as a nurse or a social worker. 44 The majority of screenings are conducted at a healthcare setting, including at health facilities (level of care not specified), 43 47 71 73 primary care health centres, 53 general hospitals, 45 54 60 61 65 specialised hospitals or clinics, 46 49 50 55-57 60 63 64 72 community-delivered healthcare 44 61 and nursing homes. 47 Other screenings take place at population or community settings, 48 52 53 59 including at home.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%